Analisis PDRB Kota Surabaya Tahun 2020-2023 Sebagai Cerminan Pertumbuhan Ekonomi Di Kota Surabaya - Yogo Subekti; Muhammad Yasin (Universitas 45 Surabaya, 2023)
The gross domestic product of a region is often used as a reference as an indicator of the success of economic growth in a region. The process of the speed of economic growth in a region is shown by using the rate of increase in GRDP (Gross Regional Domestic Product), so that the level of development of GRDP per capita achieved by the community is often a measure of the success of a region in achieving the goal of creating economic development. (Sukirno, 1981:23). This article discusses which sectors have an important role in the development of economic growth in the city of Surabaya from 2020 to 2022.